Potential Forage of Animal Feed on Rice Fields Lora Village District Mata Oleo Bombana District - Mahafardi, La Ode; Sandiah, Natsir; Aka, Rahim (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2021)
Research has been conducted for 2 months, namely March to April 2020 aims to find out the type of forage animal feed on the rice fields lora village District Mata Oleo Bombana District Southeast Sulawesi Province. Determination of research locations by purposive sampling with observation variables in the form of forage type of animal feed, botanical composition, weight of fresh materials and capacity of capacity. The results showed the type of fodder forage consists of 10 types namely Cyperus esculentus, Bixa orellana, Cyperus iria L., Fimbristylis moliaceae (L.) Vahl, Digitaria sp., Echinocloa colona, Digitaria setigera, Monochoria vaginalis, Cyperus difformis L. and Desmodium triflorum. Botanical composition with an important value comparison dominated feed forage type Cyperus esculentus (18.72) and the lowest dominance Bixa orellana (1.72). Fresh weight production is 590.40 kg/ha with a capacity of 0.3 UT/ha/month.